Design and development of smart lock system based QR-Code for library's locker at Faculty of Engineering, Universitas Riau - Yusnita Rahayu; Luthfi Afif; Ping Jack Soh (Universitas Mercu Buana, 2022)
A security system is needed to prevent theft or other criminal acts. One of the implementations of a popular security system today is the Smart Lock System. This study discusses the design of an intelligent lock system using QR Code scanning as a locker key at the Library of the Faculty of Engineering, Universitas Riau. The design of the device system consists of one piece of ESP8266 Node MCU module, one piece of 12V Power Switch Adapter, one piece of AMS 1117 module with 3.3V and 5V output voltages, three pieces of 5V Relays, three pieces of 12V Solenoids. The security system has been improved compared with existing security systems, such as verification for personal data, email notification, and level login to get theft to treat notification. This paper also measured the delay of the device system. Based on measurement results, the average delay obtained is 1.66 seconds.